Más sobre Cyperus y Kylinga en la Península Ibérica. - Castroviejo, Santiago (Acta Botanica Malacitana, 2006)
More about Cyperus and Kylinga in Spain and Portugal Palabras clave. Cyperus, Kylinga, Península ibérica. Key words. Kylinga, Cyperus, flora, Spain, Portugal.